1982
DOI: 10.1139/e82-161
|View full text |Cite
|
Sign up to set email alerts
|

Structure, petrology, and tectonic history of the Leech River complex northwest of Victoria, Vancouver Island

Abstract: The Leech River complex 45 km northwest of Victoria consists of metamorphosed pelitic rocks, sandstone, and minor volcanic rocks, chert, and conglomerate of probable Late Jurassic to Cretaceous age. The assemblage experienced two similar deformational events during which regional shortening induced macroscopic east-plunging folds and related coaxial, mesoscopic linear structures, parasitic folds, and axial-plane cleavages. Fragmentation along the developing cleavages disrupted layering and eventually led to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
92
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(107 citation statements)
references
References 17 publications
11
92
2
Order By: Relevance
“…The topographic scarps we identified are roughly parallel to the previously mapped location of the Leech River fault (Fairchild and Cowan, 1982;Massey et al, 2005), but none of the identified fault scarps coincide exactly with the fault contact between the Leech River Complex and the Metchosin Formation (Fig. 2).…”
Section: Observationssupporting
confidence: 75%
See 2 more Smart Citations
“…The topographic scarps we identified are roughly parallel to the previously mapped location of the Leech River fault (Fairchild and Cowan, 1982;Massey et al, 2005), but none of the identified fault scarps coincide exactly with the fault contact between the Leech River Complex and the Metchosin Formation (Fig. 2).…”
Section: Observationssupporting
confidence: 75%
“…Several previous authors suggest that this fault, which places Jurassic-Cretaceous schists of the Leech River Complex to the north against Eocene basalts of the Metchosin Formation to the south ( Fig. 2A) (Fairchild and Cowan, 1982;Rusmore and Cowan, 1985), was last active in the Eocene (MacLeod et al, 1977;Johnston and Acton, 2003). Yet, trenching, coring, and geophysical studies indicate multiple Quaternary ruptures of adjacent fault systems in Washington state, USA, including the Southern Whidbey Island fault, the Utsalady Point fault, and the DarringtonDevil's Mountain fault ( Fig.…”
Section: Jua N De Fuc a Stra It G E O R G I A S T R A I T Vancouver Imentioning
confidence: 81%
See 1 more Smart Citation
“…Within a northern segment that extends from southeastern Alaska to southern Vancouver Island, forearc igneous rocks are hosted in accretionary complexes, including the Pacifi c Rim and Chugach terranes (Hill et al, 1981;Fairchild and Cowan, 1982;Rusmore and Cowan, 1985;Brandon, 1989;Barker et al, 1992;Sisson and Pavlis, 1993;Haeussler et al, 1995;Harris et al, 1996;Groome, 2000). These igneous rocks consist mainly of intermediate to felsic intrusions associated with high-temperature metamorphic assemblages (Hill et al, 1981;Fairchild and Cowan, 1982;Rusmore and Cowan, 1985;Brandon, 1989;Barker et al, 1992;Sisson and Pavlis, 1993;Groome, 2000). Subordinate felsic volcanics and mafi c intrusions are present locally (Hill et al, 1981;Groome, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…On Vancouver Island, the Pacific Rim Terrane lies structurally below Wrangellia and contains a considerable section of graphitic metasediments (Brandon, 1989;Fairchild and Cowan, 1982). Paleogene Catface magmas may have ascended through and interacted with this potentially reducing country rock.…”
Section: Apatitementioning
confidence: 99%